FREQUENCY OF ABNORMAL URIC ACID LEVEL IN HAEMODIALYSIS PATIENTS. - Kunwer Naveed Mukhtar; Farheen Malik; Ayema Haque; Sobia Mansoor (ziauddin University, 2024)
Background: Hyperuricemia and hypouricemia have been implicated as a cause of high mortality in haemodialysis patients. Our study is designed to determine the frequency of abnormal Uric Acid levels in haemodialysis patients and to identify those at risk of increasing mortality. Methods: 140 End Stage Renal Disease (ESRD) patients undergoing haemodialysiswere enrolled in a retrospective cross sectional study. Uric Acid levels done as routine sampling was noted and data analyzed using SPSS for windows, version 23. All data are presented as mean ±SD. A relationship was considered statistically significant at p-values less than 0.05. Patient's age and comorbidities like Diabetes and Hypertension were noted. Patients with mean UA levels between 2.4-6 mg/dl were specified as normouricemic, above this range as hyperuricemic and below this range as hypouricemic. Results: Out of 140 patients, 71(50.7%) were males and 69(49.3%)were females. Mean age of our patient population was 56.64 ± 12.207. 56 (40%) patients were hyperuricemic and 8 (5.7%) hypouricemic. 87 (62.1%) were diabetic,122 (87.1%) were hypertensive whereas 83 (59.3%) were both hypertensive and diabetic but no notable (p> 0.05) link was found to exist between hyperuricemia and these co-morbidities. Conclusion: We report a very high frequency of abnormal Uric Acid levels in haemodialysis patients. Nearly half of our haemodialysis population is at high risk of all-cause mortality based on Uric Acid levels alone.